Urtica dioica agglutinin (a plant lectin) has a caspase-dependent apoptosis induction effect on the acute lymphoblastic leukemia cell line - Rashidbaghan, Azam; Mostafaie, Ali; Yazdani, Yaghoub; Mansouri, Kamran (Cellular and Molecular Biology, 2020)
Urtica dioica agglutinin (UDA) is a very small plant lectin with anti-prostatic activity. In this study, we investigated the effect of UDA on proliferation and apoptosis induction in human acute lymphoid leukemia (ALL) cell lines. The effect of UDA on Jurkat and Raji cell proliferation was examined by MTS assay. Distribution of cell cycle phases was determined by PI staining and apoptosis was examined with annexin V/PI and western blot. Results showed UDA treatment reduced cell proliferation in cells by inducing apoptosis. PI staining was associated with a higher percentage of the cell population in sub G1. Caspase-8 and caspase-9 dependent apoptosis occurred in Jurkat cells. Generally, UDA treatment resulted in cell death in ALL cell lines and induced apoptosis in the T-ALL cell line, Jurkat, through extrinsic and intrinsic pathways. These results may be considered as a guide to working on UDA as an anti-leukemic drug in the future.